Trans-thoracic versus trans-hiatal resection for oesophageal carcinoma: a retrospective comparative study of a single-centre case series - Baram, Aram (Cardiothorac Surg, 2020)
BACKGROUND: Oesophageal carcinoma (EC) is the eighth most common cancer. Surgery is the cornerstone of management for resectable EC. Trans-thoracic oesophagectomy (TTE) and trans-hiatal oesophagectomy (THE) are the two most widely practised procedures. Most of the related controversies are centred on both early and late post-operative complications and mortality (in terms of overall survival and cancer-free survival). This was a single-centre, retrospective, comparative study analysing the outcomes of two EC resection methods. All 87 patients underwent surgery by the same surgical team over 13 years. Consequently, 87 oesophagectomies with curative intent were performed and divided into the TTE group (group A = 47) and the THE group (group B = 40). RESULTS: The mean patient age was 65.60 ± 6.30 years in the TTE group and 63.48 ± 9.34 years in the THE group. No significant difference was found in operative time, blood loss or duration of stay in the intensive care unit. The duration of hospital stay was significantly different between the THE and TTE groups (17.25 ± 5.92 vs. 12.93 ± 3.44, respectively; P ≤ 0.001). In-hospital mortality was higher in the TTE group (9/47, 19.14%) than in the THE group (5/40, 12.5%) (P = 0.400). The mean survival rate from our series showed the superiority of group A (TTE) (65.56 months) over group B (THE) (45.01 months), with P = 0.146. CONCLUSION: No high level of evidence suggests the superiority of one surgical procedure over another. The THE procedure is less time-consuming concerning care and follow-up, and most patients were more satisfied and experienced less pain than with the TTE procedure. Both THE and TTE have comparable post-operative anastomotic complications, and they have no significant long-term survival differences.